The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s13027-023-00480-4
|View full text |Cite|
|
Sign up to set email alerts
|

Emerging role of microbiota derived outer membrane vesicles to preventive, therapeutic and diagnostic proposes

Abstract: The role of gut microbiota and its products in human health and disease is profoundly investigated. The communication between gut microbiota and the host involves a complicated network of signaling pathways via biologically active molecules generated by intestinal microbiota. Some of these molecules could be assembled within nanoparticles known as outer membrane vesicles (OMVs). Recent studies propose that OMVs play a critical role in shaping immune responses, including homeostasis and acute inflammatory respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 212 publications
0
9
0
Order By: Relevance
“…Furthermore, there is some successful clinical experience with bEVs, exemplified by the MenBVac vaccine for Neisseria meningitidis [ 95 ]. As a result of these characteristics, harnessing the immunostimulatory properties of bEVs along with additional engineering (such as incorporation of chemotherapeutic drugs and tumor-targeting ligands) comprises an area of intense research efforts [ 96 98 ].…”
Section: Microbiome Revelations Spur Interest In Bugs-as-drugs For Ca...mentioning
confidence: 99%
“…Furthermore, there is some successful clinical experience with bEVs, exemplified by the MenBVac vaccine for Neisseria meningitidis [ 95 ]. As a result of these characteristics, harnessing the immunostimulatory properties of bEVs along with additional engineering (such as incorporation of chemotherapeutic drugs and tumor-targeting ligands) comprises an area of intense research efforts [ 96 98 ].…”
Section: Microbiome Revelations Spur Interest In Bugs-as-drugs For Ca...mentioning
confidence: 99%
“…Previously, an OMV-based vaccine has been approved for use for meningococcal disease, and their small size, biological nature, and diverse surface antigens make them attractive targets for the development of other vaccines as well. , Furthermore, recent studies have shown that OMVs can be bioengineered to deliver cytotoxic payloads directly to cancer cells, making them a promising tool for targeted cancer therapy. , Moreover, Kim et al demonstrated that bioengineered OMVs can effectively reduce tumors even in the absence of a cytotoxic payload, indicating their potential as a standalone therapeutic agent, further highlighting the potential of OMVs . In addition OMVs have also shown promise as carriers for antibiotics, enzymes, and use as diagnostic agents. Nonetheless, owing to the inherent heterogeneity of OMVs, their complete utilization as therapeutics faces limitations, underscoring the need for further research and exploration.…”
Section: Introductionmentioning
confidence: 99%
“…OMVs can carry various virulence factors, such as toxins, enzymes, and lipopolysaccharides, which can be delivered to other bacteria or host cells [ 14 ]. However, they also have therapeutic potential, as they can be loaded with drugs or vaccines and used for targeted delivery [ 15 ]. Fungi-derived EVs have also been demonstrated to have therapeutic potential for modulating the immune system and delivering drugs [ 16 , 17 ].…”
mentioning
confidence: 99%